Euroregion Bílé-Biele Karpaty - Czech-Slovak cross-border cooperation - Válková, Barbora (2010)
This thesis focuses on cross-border cooperation. To set the reader into context, its history and position within European Union is mentioned here. However, the main focus is set onto the cross-border cooperation in the Czech Republic, Czech-Slovak borderland is further analyzed in detail. Using socio-economic analysis of regions of Zlín and Trenčín, particular euroregion, White Carpathian Mountains, is studied, whether socio-economical level is raised on both sides of the border as a result of this cross-border cooperation. SWOT analysis, which can point out possible directions of development of this region, is also part of this thesis. Questionnaire method is used in the conclusion of the thesis. This method has to reveal, whether this region was created on historical background, or whether it was formed more or less artificially in order to get funds.